2005
DOI: 10.1523/jneurosci.3247-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Expressing Neurons within the Retina Regulate the Proliferation of Neural Progenitors in the Circumferential Marginal Zone of the Avian Eye

Abstract: Glucagon-expressing retinal amacrine cells have been implicated in regulating postnatal ocular growth. Furthermore, experimentally accelerated rates of ocular growth increase the number of neurons added to the peripheral edge of the retina. Accordingly, we assayed whether glucagon-expressing neurons within the retina regulate the proliferation of progenitors in the circumferential marginal zone (CMZ) of the postnatal chicken eye. We found that glucagon-containing neurites are heavily clustered within the CMZ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 41 publications
(63 reference statements)
10
51
0
Order By: Relevance
“…Under normal conditions, the progenitors in the CMZ are relatively quiescent, but can be stimulated to proliferate by intraocular injections of insulin, IGF-I, EGF or Shh, and by increasing rates of ocular growth via form-deprivation [10,14,16,26,32]. Conversely, the proliferation of progenitors can be suppressed by intraocular injections of glucagon or glucagon-like peptide 1 [13]. The quiescent state of the postnatal CMZ may, in part, result from glucagon-mediated inhibitory input from a unique type of retinal neuron that has been termed "bullwhip cell" [13,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, the progenitors in the CMZ are relatively quiescent, but can be stimulated to proliferate by intraocular injections of insulin, IGF-I, EGF or Shh, and by increasing rates of ocular growth via form-deprivation [10,14,16,26,32]. Conversely, the proliferation of progenitors can be suppressed by intraocular injections of glucagon or glucagon-like peptide 1 [13]. The quiescent state of the postnatal CMZ may, in part, result from glucagon-mediated inhibitory input from a unique type of retinal neuron that has been termed "bullwhip cell" [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the proliferation of progenitors can be suppressed by intraocular injections of glucagon or glucagon-like peptide 1 [13]. The quiescent state of the postnatal CMZ may, in part, result from glucagon-mediated inhibitory input from a unique type of retinal neuron that has been termed "bullwhip cell" [13,18]. Furthermore, under normal conditions, the progenitors in the postnatal avian CMZ do not generate photoreceptors [14], and do not produce ganglion cells unless stimulated by the combination of insulin and FGF2 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is a massive accumulation of glucagon-immunoreactive neurites clustered in the CMZ. 17 Further, we found that intraocular injections of glucagon peptide inhibits the proliferation of CMZ progenitors, and inhibition of the glucagon receptor increases the proliferation of CMZ progenitors. 17 The cells that produce the terminals that ramify in the CMZ were revealed to be unique types of cells that are distinct from the GACs.…”
Section: Stem Cells Within the Retinal Margin And Nonpigmented Epithementioning
confidence: 72%
“…17 Further, we found that intraocular injections of glucagon peptide inhibits the proliferation of CMZ progenitors, and inhibition of the glucagon receptor increases the proliferation of CMZ progenitors. 17 The cells that produce the terminals that ramify in the CMZ were revealed to be unique types of cells that are distinct from the GACs. Within vertical sections of the retina, we occasionally observed unusual, glucagon-immunoreactive unipolar neurons with large somata in the INL, neurites in the distal inner plexiform layer (IPL), and axon-like structures that project toward the retinal periphery.…”
Section: Stem Cells Within the Retinal Margin And Nonpigmented Epithementioning
confidence: 72%
See 1 more Smart Citation